Corrigendum to ‘A U.S. scientific community review of carbon cycle science gaps and opportunities to better support earth system science and carbon management’ [Earth-Science Reviews 278 (2026) 1-28] - N.C. Parazoo; D. Carroll; J.B. Abshire; Y.M. Bar-On; R.A. Birdsey; A.A. Bloom; K.W. Bowman; R.K. Braghiere; L.M. Bruhwiler; B. Byrne; A. Chatterjee; D. Crisp; et al. (Earth-Science Reviews, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

A U.S. scientific community review of carbon cycle science gaps and opportunities to better support earth system science and carbon management - N.C. Parazoo; D. Carroll; J.B. Abshire; Y.M. Bar-On; R.A. Birdsey; A.A. Bloom; K.W. Bowman; R.K. Braghiere; L.M. Bruhwiler; B. Byrne; A. Chatterjee; D. Crisp; et al. (Earth-Science Reviews, 2026)

Novel Haemoproteus parasite lineage in Hooded Vultures (Necrosyrtes monachus) forms a distinct clade in Accipitriformes and highlights primer selection challenges in understudied avian hosts - Misa Shimizu; Oliver J. L. Fox; Jez Blackburn; Michael Colley; Colin Cross; Wendy James; John Jarju; Emmanuel Jatta; Naffie Sarr; Roger Walsh; Stephanie Key; Claudio Navarrete; et al. (Acta Parasitologica, 2026)

Expanding insights into plant rhabdovirus diversity through the discovery of viruses representing 32 putative novel species - Marleen Botermans; P. P. M. de Koning; M. Westenberg; I. P. Adams; K. Ben Mansour; C. Chabi-Jesus; C. de Krom; A. M. Dullemans; R. Festus; A. R. Fowkes; A. Fox; J. Freitas-Astúa; et al. (Archives of Virology, 2026)
Plant-infecting rhabdoviruses (family Rhabdoviridae , subfamily Betarhabdovirinae ) include several viruses that cause important crop diseases and are subject to phytosanitary regulation. Despite their agricultural and ecological importance, the diversity of plant rhabdoviruses and their impact on plant health remain poorly understood. Here, we report 32 tentative novel species of plant-infecting rhabdoviruses, identified via high-throughput sequencing and spanning nine established genera. The virus sequences originated from diverse hosts and geographic regions, revealing extensive diversity within the family Rhabdoviridae . Several viruses were detected independently in the same host species across multiple countries, demonstrating the practical value of data sharing for confirming host associations and gaining insight into the geographic distribution of these viruses. Our study highlights the underexplored diversity of plant rhabdoviruses and demonstrates the value of coordinated, collaborative virus discovery. With HTS now widely accessible, the challenge has shifted from virus discovery to making sequence data and metadata publicly available, and to conducting the time-consuming biological characterization often deprioritized in favour of viruses with immediate phytosanitary relevance. As a result, many findings remain unreported, leaving valuable data dormant on servers. By sharing genomic data prior to publication, we present an efficient approach to accelerate virus reporting, enable comparative analyses and advance understanding of virus diversity. We hope this collaborative effort will encourage further exploration of plant viruses, including those from hosts without discernable symptoms, supporting virus biology, taxonomy, pest risk assessments, and plant health policies.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Exposure risk of alcids to marine vessel-associated oil pollution in Western Canada - Patrick D. O'Hara; Sonya Pastran; Douglas F. Bertram; Alexandra King; Mathieu Bourbonnais; Paul Barrett; Laurie Wilson; Ken H. Morgan; Caroline H. Fox; Gary W. Kaiser; Vivian Pattison; Leh Smallshaw; et al. (Science of The Total Environment, 2026)

Hydrologic variability drives environmental and geospatial relationships in Smallmouth Bass (Micropterus dolomieu) distribution - Sarah F. Sorensen; J. Tyler Fox; Daniel D. Magoulick (Science of The Total Environment, 2026)

Effect of grape ripeness, alcohol content, and maceration duration on phenolic content and composition of cabernet sauvignon wines - Juliana Pazos; Danielle J. Fox; Apramita Devi; James F. Harbertson (Food Chemistry, 2026)

Initiation of dolutegravir vs. efavirenz on 12- and 24-month retention and viral suppression: a target trial emulation - Amy Zheng; Alana T. Brennan; Ross Greener; Emma M. Kileel; Jacob Bor; Willem D. F. Venter; Eleanor J. Murray; Pedro T. Pisa; Bridgette Goeieman; Matthew P. Fox; Mhairi Maskew (Infectious Diseases, 2026)

Formation of novel GSH-tannin adducts during red wine aging: Detection and identification using targeted mass-spectrometry - Apramita Devi; Danielle J. Fox; James F. Harbertson; Andrew L. Waterhouse (Food Research International, 2025)

From Data Deficient to Big Data in Shark Conservation - F. Ferretti; J. Jenrette; S. Moro; C. Butner; E. Fox; S. H. D. Haddock; S. J. Jorgensen; T. Hastie; F. Micheli (Fish and Fisheries, 2025)
Citizen science is increasingly harnessed worldwide to gather data otherwise requiring a prohibitive investment of funding and time. Meanwhile, the revolution in digital communication offers opportunities from crowdsourcing, big data approaches and social network mining to quickly and cost‐effectively fill major gaps in knowledge necessary to protect endangered populations. Sharks are among the most endangered and data‐poor vertebrates in the ocean. Mainly due to overfishing, many shark populations are declining worldwide, while most species lack basic abundance, distribution and life‐history data. Hence, filling knowledge gaps across taxa, ecosystems, and regions is urgently needed to increase our understanding of their ecology, develop effective conservation actions and reverse their loss. Here, we introduce a novel citizen science and crowdsourcing approach for conservation through sharkPulse, a new platform automating data ingestion and organisation to build the largest database of shark occurrence records to date. Designed to complement and extend similar biodiversity monitoring tools relying heavily on user submissions, sharkPulse aims to source large streams of online shark images and transform them into occurrence records, filling knowledge gaps in shark ecology and biology. This platform offers a blueprint to leverage AI and big data approaches, social network data mining and participatory science to efficiently and continuously source visual media materials and transform the monitoring of data‐limited marine and terrestrial animal populations.

Developmental Behavioural Plasticity and DNA Methylation Patterns in Response to Predation Stress in Trinidadian Guppies - Janay A. Fox; Simon M. Reader; Mélanie F. Guigueno; Rowan D. H. Barrett (Molecular Ecology, 2025)
Early‐life experiences can predict the environments experienced later in life, giving individuals an opportunity to develop adaptive behaviour appropriate to a likely future environment. Epigenetic mechanisms such as DNA methylation (DNAm) have been implicated in developmental behavioural plasticity; however, studies investigating this possibility are limited in taxonomic breadth and ecological relevance. We investigated the impact of early‐life exposure to predation stress on behaviour and DNAm in the brains of Trinidadian guppies ( Poecilia reticulata ). We exposed guppies throughout development to either an alarm cue (conspecific skin extract), inducing predation stress, or a control cue (water) for 8 weeks and then raised them to adulthood under identical conditions. Then, we conducted two behavioural assays, an open‐field and a grouping test, before performing whole‐genome bisulfite sequencing on whole brains. Guppies exposed to the alarm cue during development exhibited increased grouping (shoaling) in adulthood compared to those exposed to the control treatment, but there were no detectable impacts on activity, boldness, or exploratory behaviour. We also identified stable shifts in brain DNAm in response to developmental alarm cue exposure in genes involved in behavioural regulation. Some differentially methylated sites were significantly associated with shoaling propensity in both males and females. Additionally, males and females differed in the magnitude of DNAm responses and the genes impacted, suggesting distinct roles for DNAm between the sexes. This study shows how early‐life predation stress can induce behavioural changes in adulthood and that shifts in neural DNAm could be an underlying mechanism responsible for these changes.

Measuring the social impact of City-region food system initiatives (CRFSIs): A systematic review of indicators and metrics - K. Specht; C. Iodice; F. Monticone; P. Tonini; M. Petruzzelli; L. Carotti; R. Fox-Kämper; S. Toboso-Chavero; F. Orsini; A. Samoggia; M. Vittuari (Sustainable Cities and Society, 2025)

Age and style of intraplate basaltic volcanism at Stanley, northwest Tasmania, Australia - J. M. Fox; J. McPhie; R. J. Carey; F. Jourdan (Australian Journal of Earth Sciences, 2025)

Multi-domain magnetic particles in speleothems as a proxy for past cave-stream flooding: A 33 kyr record from central North Island, Aotearoa New Zealand - Bethany R.S. Fox; Ioan Lascu; Richard Harrison; Andrew R. Pearson; John Hellstrom; Sebastian F.M. Breitenbach; Joshua F. Einsle; Joy Muraszko; Adam Hartland (Quaternary Science Reviews, 2025)

Establishing performance criteria for evaluating watershed-scale sediment and nutrient models at fine temporal scales - Aayush Pandit; Sarah Hogan; David T. Mahoney; William I. Ford; James F. Fox; Christopher Wellen; Admin Husic (Water Research, 2025)

Coral reef thermal microclimates mapped from the International Space Station - J. Longenecker; F. Benzoni; N. Dunn; H. E. Fox; A. Gleason; D. Otis; V. Chirayath; N. Oury; S. J. Purkis (Coral Reefs, 2025)
Satellite sea surface temperature (SST) is critical for describing marine environments. Traditional SST data, such as those provided by the Group for High Resolution Sea Surface Temperature (GHRSST) program, are valuable, but have a relatively coarse spatial resolution for mapping coral reef thermal environments. Hence, fine resolution SST from orbit would be of great utility to the coral reef research community and speed the pathway to an increased understanding of how, when, and where thermal stress afflicts individual reefs. Such data would support adaptive management, especially so for the design of marine protected areas. Flying aboard the International Space Station, the NASA ECOsystem Spaceborne Thermal Radiometer Experiment on Space Station (ECOSTRESS) instrument may already fill this niche with a spatial resolution 204 times finer than GHRSST. To evaluate ECOSTRESS thermal data over reef environments, we deployed 21 temperature loggers over three years across two reef sites in the Red Sea. We compared temperature retrievals from both the coarse resolution GHRSST and the fine resolution, experimental, ECOSTRESS, to this in-situ logger dataset. While temperature data from both orbital platforms correlated strongly with the logger recordings, only ECOSTRESS, with its 70-m pixels, could construct thermal microclimate maps capturing the dynamic temperature fluctuations experienced by our studied reefs. We contend that ECOSTRESS represents a significant advancement in the capability to monitor heat stress on reefs from orbit.

Cooperation by harvester ant queens brings direct energetic benefits during colony founding - Rebecca M. Clark; Trevor P. Fox; Jennifer H. Fewell; Jon F. Harrison (Behavioral Ecology and Sociobiology, 2025)
Cooperative behavior by nonrelatives is an evolutionary puzzle, because costs of cooperation are often strong while selective factors favoring cooperative groups remain unclear. In some populations of the seed harvester ant P ogonomyrmex californicus , unrelated queens form groups at colony founding (pleometrosis), whereas in other populations, colonies are initiated by single queens (haplometrosis). We tested the hypothesis that energetic savings of grouping contribute a benefit that may enhance queen success during colony founding and early growth for pleometrotic colonies. We measured metabolic rates and locomotor activity of individuals or pairs of freshly collected, newly mated P. californicus queens from pleometrotic and haplometrotic populations. Population source did not significantly affect metabolic rates, but paired queens from both populations had mass-specific metabolic rates only 86% of those of individual queens. The metabolic effect of grouping was not explained by differences in locomotion. To test whether this degree of energetic saving could be biologically significant, we assessed metabolic rate, body mass, and egg production for pleometrotic pairs at four time points of colony founding and compared the energetic content of stored lipid to energy use up to the point of worker emergence. Metabolic rates dropped over time for queens, as did body mass, and gas exchange switched from continuous to discontinuous, suggestive of metabolic suppression. Total joules required for queens to reach the worker emergence stage were 1.5 times the energy content of stored lipids, consistent with the need for foraging for these queens, and supporting the hypothesis that energetic savings of grouping can be beneficial by extending energetic stores and reducing the need for risky foraging.

Exercise recovers weight gain, but not increased impulsive choice, caused by a high-fat diet - Keenan F. Wilson; Adam E. Fox (Appetite, 2024)

Response time of fast flowing hydrologic pathways controls sediment hysteresis in a low-gradient watershed, as evidenced from tracer results and machine learning models - Arlex Marin-Ramirez; David Tyler Mahoney; Brenden Riddle; Leonie Bettel; James F. Fox (Journal of Hydrology, 2024)

Comparison of pre-fermentation and post-fermentations alcohol adjustments on aromatic chemistry and sensory composition of Sauvignon blanc wine - Danielle J. Fox; James F. Harbertson (Food Chemistry, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Risk factors affecting the feeding site predilection of ticks on cattle in Ghana - Seth Offei Addo; Ronald Essah Bentil; Mba-tihssommah Mosore; Eric Behene; Julian Adinkrah; Janice Tagoe; Clara Yeboah; Bernice Olivia Ama Baako; Dorcas Atibila; Sandra Abankwa Kwarteng; Kwaku Poku-Asante; Ellis Owusu-Darbo; et al. (Experimental and Applied Acarology, 2024)
Ticks are important disease vectors affecting animal health and causing substantial economic loss, especially in the tropics and subtropics. To examine the tick burden of cattle and associated risk factors for tick infestation, ticks were collected from 388 cattle within five regions in Ghana. Most of the cattle were males (50.3%) and generally older than 3 years (65%). Of the animals sampled, 2187 ticks were collected with a mean tick burden of 5.6 ticks per cattle, and the average tick burden on the udder/scrotum being significantly higher than in the anal region (Generalized Linear Mix Model [GLMM], p = 0.01197). The tick species identified were predominantly Amblyomma variegatum (42.6%) and Hyalomma rufipes (26.2%). High proportions of cattle examined were found to have A. variegatum infesting the udder/scrotum. Furthermore, H. rufipes infested mostly the anal region compared to other examined body parts (OR 14.8, 95% CI 8.6–25.4, p < 0.001). Using the GLMM, tick abundance was found to be significantly higher in cattle older than 3 years. The tick burden in the udder/scrotum was higher than that from the chest and leg/thigh of the cattle (GLMM, p < 0.05). The tick burden at the anal region was also significantly higher than the leg/thigh and chest. This study indicates that the preferred attachment sites of ticks on cattle are species-dependent and effective treatment with acaricides should take into consideration the udder/scrotum and anal regions as well as prioritizing older cattle.

A supermatrix phylogeny of the world’s bees (Hymenoptera: Anthophila) - Patricia Henríquez-Piskulich; Andrew F. Hugall; Devi Stuart-Fox (Molecular Phylogenetics and Evolution, 2024)

The influence of regional wind patterns on air quality during forest fires near Sydney, Australia - Michael A. Storey; Owen F. Price; Paul Fox-Hughes (Science of The Total Environment, 2023)

Wet air oxidation of HTL aqueous waste - Uriah J. Kilgore; Senthil Subramaniam; Samuel P. Fox; Dylan J. Cronin; Mond F. Guo; Andrew J. Schmidt; Karthikeyan K. Ramasamy; Michael R. Thorson (Biomass and Bioenergy, 2023)

Summer and autumn movement ecology of native brook trout (Salvelinus fontinalis) in urban headwater streams of Eastern North America - Lee F. G. Gutowsky; Scott G. Blair; Steven J. Cooke; Michael G. Fox (Hydrobiologia, 2023)

Investigating scent communication and latrine use to inform translocation of the Tasmanian devil - Debra M. Shier; Gregory F. Grether; Elizabeth E. Reid-Wainscoat; Samantha Fox; David Pemberton; Jodie Elmer; Ronald R. Swaisgood (Behavioral Ecology and Sociobiology, 2023)
Translocation programs for endangered mammalian carnivores face numerous challenges, including the potential for lethal interactions between releasees and resident conspecifics. Here we evaluate whether familiarizing residents with the scent of releasees might be an effective strategy for reducing aggression following Tasmanian devil ( Sarcophilus harrisii ) translocation. Tasmanian devils live in loose social networks in which residents have overlapping home ranges and use communal latrines. In a controlled ex situ experiment, we first found that devils readily distinguished between the feces of familiar and unfamiliar conspecifics. Next, we swapped feces between devils slated for release and wild resident devils, seeding a random half of communal latrines in the wild with the feces of releasee prior to their release, and used motion-activated video cameras to record devil visits. Wild resident devil visitation frequency and olfactory communication behaviors initially increased at experimental latrine sites where feces were deposited but not at control sites. After release, the translocated devils used both types of latrine sites and spent more time investigating experimental sites, but investigatory and scent-marking behaviors of the wild resident devils decreased, suggesting that they had become familiar with the releasees through scent. We further show that Tasmanian devil latrine sites are strongly associated with ecotones and the presence of shrubs. These findings contribute to our understanding of Tasmanian devil scent ecology and suggest that devil translocations conducted into existing populations would benefit from familiarization through latrine scent manipulation. More broadly, our results suggest an important role for scent ecology in carnivore translocation programs. Significance statement A conservation management action that is being trialed for endangered Tasmanian devils is to breed devils in human care and reinforce dwindling small resident populations through translocation. However, with limited social interactions, unfamiliar devils may interact aggressively, increasing injury and reducing translocation success. Scent communication is nearly ubiquitous in mammals and may be a prerequisite for management of social aggression. Almost nothing is known about devil scent ecology. Our discovery that devils become familiarized with conspecifics through feces, combined with findings that wild devils that are exposed to translocated devil scent in advance of release show reduced interest in scent-seeded latrines, even after new devils are released, suggests that devils familiarized through scent in advance of relocation may exhibit reduced aggression. These results provide an avenue for improving the success of translocations for devils and other at-risk solitary mammalian carnivores.

Revised stratigraphy and first geochronology of the Miocene submarine volcanic succession at Kennaook/Cape Grim, northwestern Tasmania - J. M. Fox; J. McPhie; R. J. Carey; F. Jourdan (Australian Journal of Earth Sciences, 2023)

The effects of light pollution on migratory animal behavior - Carolyn S. Burt; Jeffrey F. Kelly; Grace E. Trankina; Carol L. Silva; Ali Khalighifar; Hank C. Jenkins-Smith; Andrew S. Fox; Kurt M. Fristrup; Kyle G. Horton (Trends in Ecology & Evolution, 2023)

Co-alteration Network Architecture of Major Depressive Disorder: A Multi-modal Neuroimaging Assessment of Large-scale Disease Effects - Jodie P. Gray; Jordi Manuello; Aaron F. Alexander-Bloch; Cassandra Leonardo; Crystal Franklin; Ki Sueng Choi; Franco Cauda; Tommaso Costa; John Blangero; David C. Glahn; Helen S. Mayberg; Peter T. Fox (Neuroinformatics, 2023)

Disentangling thermal from alternative drivers of reflectance in jewel beetles: A macroecological study - Lu‐Yi Wang; Amanda M. Franklin; Andrew F. Hugall; Iliana Medina; Devi Stuart‐Fox (Global Ecology and Biogeography, 2023)
Aim To predict future colour–climate relationships, it is important to distinguish thermal drivers of reflectance from other evolutionary drivers. We aimed to achieve this by comparing relationships between climate and coloration in ultraviolet–visible (UV–Vis) and near‐infrared (NIR) light, separately. Location Samples were distributed primarily across Australia and North America, with some from Africa and Asia. Major taxa studied Coleoptera: Buprestidae. Methods We used jewel beetles as models to identify climatic drivers of reflectance, because jewel beetles have highly diverse coloration and a wide distribution and are often active in hot conditions. Specifically, we tested the association between climate, body size and reflectance using a phylogenetic comparative analysis for three wavebands (UV–Vis, NIR and total). Results Reflectance of jewel beetles was more strongly predicted by body size than by climate. NIR reflectance and total reflectance were not associated with climate, but larger beetles had higher NIR reflectance. For UV–Vis reflectance, small beetles were darker in warmer and more humid environments, whereas there was no association with climate for large beetles. Main conclusions Our study suggests that variation in reflectance of jewel beetles is not driven by thermal requirements and highlights the importance of considering NIR reflectance when evaluating explanations of the effects of colour on thermoregulation.

Global patterns of illegal marine turtle exploitation - Jesse F. Senko; Kayla M. Burgher; Maria del Mar Mancha‐Cisneros; Brendan J. Godley; Irene Kinan‐Kelly; Trevor Fox; Frances Humber; Volker Koch; Andrew T. Smith; Bryan P. Wallace (Global Change Biology, 2022)
Human exploitation of wildlife for food, medicine, curios, aphrodisiacs, and spiritual artifacts represents a mounting 21st‐century conservation challenge. Here, we provide the first global assessment of illegal marine turtle exploitation across multiple spatial scales (i.e., Regional Management Units [RMUs] and countries) by collating data from peer‐reviewed studies, grey literature, archived media reports, and online questionnaires of in‐country experts spanning the past three decades. Based on available information, we estimate that over 1.1 million marine turtles were exploited between 1990 and 2020 against existing laws prohibiting their use in 65 countries or territories and in 44 of the world's 58 marine turtle RMUs, with over 44,000 turtles exploited annually over the past decade. Exploitation across the 30‐year period primarily consisted of green (56%) and hawksbill (39%) turtles when identified by species, with hawksbills (67%) and greens (81%) comprising the majority of turtles exploited in the 1990s and 2000s, respectively, and both species accounting for similar levels of exploitation in the 2010s. Although there were no clear overarching trends in the magnitude or spatial patterns of exploitation across the three decades, there was a 28% decrease in reported exploitation from the 2000s to the 2010s. The 10 RMUs with the highest exploitation in the 2010s included seven green and three hawksbill turtle RMUs, with most reported exploitation occurring in RMUs that typically exhibit a low risk of population decline or loss of genetic diversity. Over the past decade, the number of RMUs with “moderate” or “high” exploitation impact scores decreased. Our assessment suggests that illegal exploitation appears to have declined over the past decade and, with some exceptions, is primarily occurring in large, stable, and genetically diverse marine turtle populations.

Benthic assemblages are more predictable than fish assemblages at an island scale - Stuart A. Sandin; Esmeralda Alcantar; Randy Clark; Ramón de León; Faisal Dilrosun; Clinton B. Edwards; Andrew J. Estep; Yoan Eynaud; Beverly J. French; Michael D. Fox; Dave Grenda; Scott L. Hamilton; et al. (Coral Reefs, 2022)
Decades of research have revealed relationships between the abundance of coral reef taxa and local conditions, especially at small scales. However, a rigorous test of covariation requires a robust dataset collected across wide environmental or experimental gradients. Here, we surveyed spatial variability in the densities of major coral reef functional groups at 122 sites along a 70 km expanse of the leeward, forereef habitat of Curaçao in the southern Caribbean. These data were used to test the degree to which spatial variability in community composition could be predicted based on assumed functional relationships and site-specific anthropogenic, physical, and ecological conditions. In general, models revealed less power to describe the spatial variability of fish biomass than cover of reef builders (R 2 of best-fit models: 0.25 [fish] and 0.64 [reef builders]). The variability in total benthic cover of reef builders was best described by physical (wave exposure and reef relief) and ecological (turf algal height and coral recruit density) predictors. No metric of anthropogenic pressure was related to spatial variation in reef builder cover. In contrast, total fish biomass showed a consistent (albeit weak) association with anthropogenic predictors (fishing and diving pressure). As is typical of most environmental gradients, the spatial patterns of both fish biomass density and reef builder cover were spatially autocorrelated. Residuals from the best-fit model for fish biomass retained a signature of spatial autocorrelation while the best-fit model for reef builder cover removed spatial autocorrelation, thus reinforcing our finding that environmental predictors were better able to describe the spatial variability of reef builders than that of fish biomass. As we seek to understand spatial variability of coral reef communities at the scale of most management units (i.e., at kilometer- to island-scales), distinct and scale-dependent perspectives will be needed when considering different functional groups.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Environmental gradients predict the ratio of environmentally acquired carotenoids to self‐synthesised pteridine pigments - Devi Stuart‐Fox; Katrina J. Rankin; Adrian Lutz; Adam Elliott; Andrew F. Hugall; Claire A. McLean; Iliana Medina (Ecology Letters, 2021)
Carotenoids are important pigments producing integument colouration; however, their dietary availability may be limited in some environments. Many species produce yellow to red hues using a combination of carotenoids and self‐synthesised pteridine pigments. A compelling hypothesis is that pteridines replace carotenoids in environments where carotenoid availability is limited. To test this hypothesis, we quantified concentrations of five carotenoid and six pteridine pigments in multiple skin colours and individuals from 27 species of agamid lizards. We show that environmental gradients predict the ratio of carotenoids to pteridines; carotenoid concentrations are lower and pteridine concentrations higher in arid environments with low vegetation productivity. Both carotenoid and pteridine pigments were present in all species, but only pteridine concentrations explained colour variation among species and there were no correlations between carotenoid and pteridine pigments with a similar hue. These results suggest that in arid environments, where carotenoids are likely limited, species may compensate by synthesising more pteridines but do not necessarily replace carotenoids with pteridines of similar hue.

Advances in Observing and Understanding Small-Scale Open Ocean Circulation During the Gulf of Mexico Research Initiative Era - Eric A. D'Asaro; Daniel F. Carlson; Marcelo Chamecki; Ramsey R. Harcourt; Brian K. Haus; Baylor Fox-Kemper; M. Jeroen Molemaker; Andrew C. Poje; Di Yang (Frontiers in Marine Science, 2020)

The U.S. Climate Resilience Toolkit: evidence of progress - Edward P. Gardiner; David D. Herring; James F. Fox (Climatic Change, 2019)

Effects of ecological and anthropogenic factors on waterbird abundance at a Ramsar Site in the Yangtze River Floodplain - Yong Zhang; Anthony D. Fox; Lei Cao; Qiang Jia; Changhu Lu; Herbert H. T. Prins; Willem F. de Boer (Ambio, 2019)

Surface Ocean Dispersion Observations From the Ship-Tethered Aerostat Remote Sensing System - Daniel F. Carlson; Tamay Özgökmen; Guillaume Novelli; Cedric Guigand; Henry Chang; Baylor Fox-Kemper; Jean Mensa; Sanchit Mehta; Erick Fredj; Helga Huntley; A. D. Kirwan; Maristella Berta; et al. (Frontiers in Marine Science, 2018)

Landscape genetics of the Tasmanian devil: implications for spread of an infectious cancer - Andrew Storfer; Brendan Epstein; Menna Jones; Steven Micheletti; Stephen F. Spear; Shelly Lachish; Samantha Fox (Conservation Genetics, 2017)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

The Social, Historical, and Institutional Contingencies of Dam Removal - F. J. Magilligan; C. S. Sneddon; C. A. Fox (Environmental Management, 2017)

Adapting astronomical source detection software to help detect animals in thermal images obtained by unmanned aerial systems - S. N. Longmore; R. P. Collins; S. Pfeifer; S. E. Fox; M. Mulero-Pázmány; F. Bezombes; A. Goodwin; M. De Juan Ovelar; J. H. Knapen; S. A. Wich (International Journal of Remote Sensing, 2017)

A review of parasites in the Tasmanian devil (Sarcophilus harrisii) - Liana F. Wait; Sarah Peck; Samantha Fox; Michelle L. Power (Biodiversity and Conservation, 2017)

Why geese benefit from the transition from natural vegetation to agriculture - Anthony D. Fox; Kenneth F. Abraham (Ambio, 2017)

A Galaxy-based bioinformatics pipeline for optimised, streamlined microsatellite development from Illumina next-generation sequencing data - Sarah M. Griffiths; Graeme Fox; Peter J. Briggs; Ian J. Donaldson; Simon Hood; Pen Richardson; George W. Leaver; Nathan K. Truelove; Richard F. Preziosi (Conservation Genetics Resources, 2016)

Natural hazards in Australia: extreme bushfire - Jason J. Sharples; Geoffrey J. Cary; Paul Fox-Hughes; Scott Mooney; Jason P. Evans; Michael-Shawn Fletcher; Mike Fromm; Pauline F. Grierson; Rick McRae; Patrick Baker (Climatic Change, 2016)

Precipitation in the EURO-CORDEX $$0.11^{° }$$ 0 . 11 ∘ and $$0.44^{° }$$ 0 . 44 ∘ simulations: high resolution, high benefits? - A. F. Prein; A. Gobiet; H. Truhetz; K. Keuler; K. Goergen; C. Teichmann; C. Fox Maule; E. van Meijgaard; M. Déqué; G. Nikulin; R. Vautard; A. Colette; et al. (Climate Dynamics, 2016)

Fish community dynamics following dam removal in a fragmented agricultural stream - Matthew S. Kornis; Brian C. Weidel; Stephen M. Powers; Matthew W. Diebel; Timothy J. Cline; Justin M. Fox; James F. Kitchell (Aquatic Sciences, 2015)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Species richness declines and biotic homogenisation have slowed down for NW ‐European pollinators and plants - Luísa Gigante Carvalheiro; William E. Kunin; Petr Keil; Jesus Aguirre‐Gutiérrez; Willem Nicolaas Ellis; Richard Fox; Quentin Groom; Stephan Hennekens; Wouter Van Landuyt; Dirk Maes; Frank Van de Meutter; Denis Michez; et al. (Ecology Letters, 2013)
Concern about biodiversity loss has led to increased public investment in conservation. Whereas there is a widespread perception that such initiatives have been unsuccessful, there are few quantitative tests of this perception. Here, we evaluate whether rates of biodiversity change have altered in recent decades in three European countries (Great Britain, Netherlands and Belgium) for plants and flower visiting insects. We compared four 20‐year periods, comparing periods of rapid land‐use intensification and natural habitat loss (1930–1990) with a period of increased conservation investment (post‐1990). We found that extensive species richness loss and biotic homogenisation occurred before 1990, whereas these negative trends became substantially less accentuated during recent decades, being partially reversed for certain taxa (e.g. bees in Great Britain and Netherlands). These results highlight the potential to maintain or even restore current species assemblages (which despite past extinctions are still of great conservation value), at least in regions where large‐scale land‐use intensification and natural habitat loss has ceased.

An evaluation of the serotonin system and perseverative, compulsive, stereotypical, and hyperactive behaviors in dopamine transporter (DAT) knockout mice - Meredith A. Fox; Micaella G. Panessiti; F. Scott Hall; George R. Uhl; Dennis L. Murphy (Psychopharmacology, 2013)

Effects of the combination of metyrapone and oxazepam on intravenous nicotine self-administration in rats - Nicholas E. Goeders; Ami Cohen; Barbara S. Fox; Marc R. Azar; Olivier George; George F. Koob (Psychopharmacology, 2012)

Limitations and potentials of dual-purpose cow herds in Central Coastal Veracruz, Mexico - Victor Antonio Absalón-Medina; Robert W. Blake; Danny Gene Fox; Francisco I. Juárez-Lagunes; Charles F. Nicholson; Eduardo G. Canudas-Lara; Bertha L. Rueda-Maldonado (Tropical Animal Health and Production, 2012)

Economic analysis of alternative nutritional management of dual-purpose cow herds in central coastal Veracruz, Mexico - Victor Antonio Absalón-Medina; Charles F. Nicholson; Robert W. Blake; Danny Gene Fox; Francisco I. Juárez-Lagunes; Eduardo G. Canudas-Lara; Bertha L. Rueda-Maldonado (Tropical Animal Health and Production, 2012)

Enhancing the identification of genetic loci and transgressive segregants for preharvest sprouting resistance in a durum wheat population - R. E. Knox; F. R. Clarke; J. M. Clarke; S. L. Fox; R. M. DePauw; A. K. Singh (Euphytica, 2012)

Intra‐population variability of life‐history traits and growth during range expansion of the invasive round goby, Neogobius melanostomus - L. F. G. GUTOWSKY; M. G. FOX (Fisheries Management and Ecology, 2012)
Fish can undergo changes in their life‐history traits that correspond with local demographic conditions. Under range expansion, a population of non‐native fish might then be expected to exhibit a suite of life‐history traits that differ between the edge and the centre of the population’s geographic range. To test this hypothesis, life‐history traits of an expanding population of round goby, Neogobius melanostomus (Pallas), in early and newly established sites in the Trent River (Ontario, Canada) were compared in 2007 and 2008. Round goby in the area of first introduction exhibited a significant decrease in age at maturity, increased length at age 1 and they increased in GSI from 2007 to 2008. While individuals at the edges of the range exhibited traits that promote population growth under low intraspecific density, yearly variability in life‐history traits suggests that additional processes such as declining density and fluctuating food availability are influencing the reproductive strategy and growth of round goby during an invasion.

Occupation, body size and sex ratio of round goby (Neogobius melanostomus) in established and newly invaded areas of an Ontario river - Lee F. G. Gutowsky; Michael G. Fox (Hydrobiologia, 2011)

Diet composition and consumption rate in round goby (Neogobius melanostomus) in its expansion phase in the Trent River, Ontario - Graham D. Raby; Lee F. G. Gutowsky; Michael G. Fox (Environmental Biology of Fishes, 2010)

Conservation genetics of the alligator snapping turtle: cytonuclear evidence of range-wide bottleneck effects and unusually pronounced geographic structure - A. A. Echelle; J. C. Hackler; J. B. Lack; S. R. Ballard; J. Roman; S. F. Fox; D. M. Leslie; R. A. Van Den Bussche (Conservation Genetics, 2010)

Termites create spatial structure and govern ecosystem function by affecting N 2 fixation in an East African savanna - Kena Fox-Dobbs; Daniel F. Doak; Alison K. Brody; Todd M. Palmer (Ecology, 2010)
The mechanisms by which even the clearest of keystone or dominant species exert community‐wide effects are only partially understood in most ecosystems. This is especially true when a species or guild influences community‐wide interactions via changes in the abiotic landscape. Using stable isotope analyses, we show that subterranean termites in an East African savanna strongly influence a key ecosystem process: atmospheric nitrogen fixation by a monodominant tree species and its bacterial symbionts. Specifically, we applied the 15 N natural abundance method in combination with other biogeochemical analyses to assess levels of nitrogen fixation by Acacia drepanolobium and its effects on co‐occurring grasses and forbs in areas near and far from mounds and where ungulates were or were not excluded. We find that termites exert far stronger effects than do herbivores on nitrogen fixation. The percentage of nitrogen derived from fixation in Acacia drepanolobium trees is higher (55–80%) away from mounds vs. near mounds (40–50%). Mound soils have higher levels of plant available nitrogen, and Acacia drepanolobium may preferentially utilize soil‐based nitrogen sources in lieu of fixed nitrogen when these sources are readily available near termite mounds. At the scale of the landscape, our models predict that termite/soil derived nitrogen sources influence >50% of the Acacia drepanolobium trees in our system. Further, the spatial extent of these effects combine with the spacing of termite mounds to create highly regular patterning in nitrogen fixation rates, resulting in marked habitat heterogeneity in an otherwise uniform landscape. In summary, we show that termite‐associated effects on nitrogen processes are not only stronger than those of more apparent large herbivores in the same system, but also occur in a highly regular spatial pattern, potentially adding to their importance as drivers of community and ecosystem structure.

Comparison of defined culture systems for feeder cell free propagation of human embryonic stem cells - Veronika Akopian; Peter W. Andrews; Stephen Beil; Nissim Benvenisty; Jennifer Brehm; Megan Christie; Angela Ford; Victoria Fox; Paul J. Gokhale; Lyn Healy; Frida Holm; Outi Hovatta; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

Termites, vertebrate herbivores, and the fruiting success of Acacia drepanolobium - Alison K. Brody; Todd M. Palmer; Kena Fox-Dobbs; Dan F. Doak (Ecology, 2010)
In African savannas, vertebrate herbivores are often identified as key determinants of plant growth, survivorship, and reproduction. However, plant reproduction is likely to be the product of responses to a suite of abiotic and biotic factors, including nutrient availability and interactions with antagonists and mutualists. In a relatively simple system, we examined the role of termites (which act as ecosystem engineers—modifying physical habitat and creating islands of high soil fertility), vertebrate herbivores, and symbiotic ants, on the fruiting success of a dominant plant, Acacia drepanolobium , in East African savannas. Using observational data, large‐scale experimental manipulations, and analysis of foliar N, we found that Acacia drepanolobium trees growing at the edge of termite mounds were more likely to reproduce than those growing farther away, in off‐mound soils. Although vertebrate herbivores preferentially used termite mounds as demonstrated by dung deposits, long‐term exclusion of mammalian grazers did not significantly reduce A. drepanolobium fruit production. Leaf N was significantly greater in trees growing next to mounds than in those growing farther away, and this pattern was unaffected by exclusion of vertebrates. Thus, soil enrichment by termites, rather than through dung and urine deposition by large herbivores, is of primary importance to fruit production near mounds. Across all mound–herbivore treatment combinations, trees that harbored Crematogaster sjostedti were more likely to fruit than those that harbored one of the other three ant species. Although C. sjostedti is less aggressive than the other ants, it tends to inhabit large, old trees near termite mounds which are more likely to fruit than smaller ones. Termites play a key role in generating patches of nutrient‐rich habitat important to the reproductive success of A. drepanolobium in East African savannas. Enhanced nutrient acquisition from termite mounds appears to allow plants to tolerate herbivory and the reduced defense by a relatively ineffective ant partner. Our results underscore the importance of simultaneously examining top‐down and bottom‐up effects to understand those factors most important to plant reproductive success.

Isolation of microsatellites via enrichment and a sequence tagged method in a South American lizard with suspected parental care, Liolaemus leopardinus - Andrew R. Murphy; Michael G. Gardner; Stanley F. Fox (Conservation Genetics Resources, 2009)

Rapid Evolution in the Wild: Changes in Body Size, Life‐History Traits, and Behavior in Hunted Populations of the Japanese Mamushi Snake - KIYOSHI SASAKI; STANLEY F. FOX; DAVID DUVALL (Conservation Biology, 2009)
Rapid evolution caused by human exploitation of wildlife is not usually addressed in studies of the impacts of such exploitation despite its direct relevance to population persistence. Japanese mamushi ( Gloydius blomhoffii ), an endemic venomous snake of the Japanese archipelago, has been heavily hunted by humans, and many populations appear to be declining or are already extirpated. We compared local populations that have been hunted regularly with populations that have not been hunted. Mamushi in hunted populations were smaller, had fewer vertebrae, produced more and smaller offspring, had increased reproductive effort among smaller females, and in nature fled at greater distances from an approaching human and were less defensive than mamushi in unhunted populations, as predicted from life‐history theory. Heritability estimates for body size, number of vertebrae, and antipredator behavior were statistically significant, and neonates from hunted sites showed the same distribution of altered characters (compared with those from unhunted sites) as adults. Thus, distribution of the divergent trait between hunted and unhunted sites appeared in part to be genetically based, which suggests rapid evolution to human predation pressures. Trait distributions in hunted populations probably deviate from naturally (as opposed to anthropogenically) selected optima and, therefore, may have long‐term negative repercussions on population persistence. Because rapid evolution affects a suite of parameters that characterize exploited populations, accurate understanding of the impacts of exploitation and effective resource management and conservation can only be achieved if evolutionary consequences are considered explicitly.

Chronic Methamphetamine Induces Structural Changes in Frontal Cortex Neurons and Upregulates Type I Interferons - Alice Coutinho; Claudia Flynn; Tricia H. Burdo; Ronald F. Mervis; Howard S. Fox (Journal of Neuroimmune Pharmacology, 2008)

NeuroAIDS, Drug Abuse, and Inflammation: Building Collaborative Research Activities - Joan W. Berman; Monica J. Carson; Linda Chang; Brian M. Cox; Howard S. Fox; R. Gilberto Gonzalez; Glen R. Hanson; Kurt F. Hauser; Wen-Zhe Ho; Jau-Shyong Hong; Eugene O. Major; William F. Maragos; et al. (Journal of Neuroimmune Pharmacology, 2006)

The importance of individual behaviour for successful settlement of juvenile plaice ( Pleuronectes platessa L.): a modelling and field study in the eastern Irish Sea - C. J. FOX; P. MCCLOGHRIE; E. F. YOUNG; R. D. M. NASH (Fisheries Oceanography, 2006)
To study the transport of plaice ( Pleuronectes platessa L.) eggs and larvae in the eastern Irish Sea, we constructed a 3D‐baroclinic physical model and coupled it to a particle‐tracking scheme that allowed aspects of larval behaviour to be simulated. Starting positions for eggs were based upon data from a series of ichthyoplankton surveys and final positions were compared with results of settled plaice distributions from two beam trawl surveys conducted on beaches around the eastern Irish Sea. If simulated larval behaviour was limited to passive drift or horizontal swimming, the particles diffused away from the spawning areas but failed to reach nursery grounds in significant numbers (85–90% remaining offshore). In contrast, switching on circatidal vertical swimming significantly increased the numbers of larvae reaching the coast (only 23–30% remained offshore). Particles tended to accumulate in bays and estuaries and this pattern compared well with the distribution of settled plaice from the field surveys. Studies in the southern North Sea (where spawning and nursery grounds are widely separated) have also demonstrated the importance of selective tidal stream transport for successful recruitment of settling plaice to nursery grounds. Although our understanding of the ontogeny of this behaviour is still poor, the model results presented suggest that this aspect of behaviour is a key factor influencing plaice settlement success.

Indole-3-carbinol-induced death in cancer cells involves EGFR downregulation and is exacerbated in a 3D environment - E. P. Moiseeva; L. H. Fox; L. M. Howells; L. A. F. Temple; M. M. Manson (Apoptosis, 2006)

Development of the dopamine transporter selective RTI-336 as a pharmacotherapy for cocaine abuse - F. Ivy Carroll; James L. Howard; Leonard L. Howell; Barbara S. Fox; Michael J. Kuhar (The AAPS Journal, 2006)

The Anthracen-9-ylmethyloxy Unit: An Underperforming Motif Within the Fluorescent PET (Photoinduced Electron Transfer) Sensing Framework - David C. Magri; John F. Callan; A. Prasanna de Silva; David B. Fox; Nathan D. McClenaghan; K. R. A. Samankumara Sandanayake (Journal of Fluorescence, 2005)

Genetic analysis of pre-harvest sprouting in a durum wheat cross - R. E. Knox; F. R. Clarke; J. M. Clarke; S. L. Fox (Euphytica, 2005)

Strategic approach to mitigating weather induced defects of wheat quality - F. R. Clarke; J. M. Clarke; R. M. DePauw; M. R. Fernandez; S. Fox; J. Gilbert; G. Humphreys; R. E. Knox; T. N. McCaig; D. Procunier; M. Sissons; D. Somers (Euphytica, 2005)

Impact of predation on establishment of the soybean aphid, Aphis glycines in soybean, Glycine max - Tyler B. Fox; Douglas A. Landis; Fernando F. Cardoso; Christina D. Difonzo (BioControl, 2005)

Solution structure of T4moC, the Rieske ferredoxin component of the toluene 4-monooxygenase complex - Lars Skjeldal; Francis C. Peterson; Jurgen F. Doreleijers; Luke A. Moe; Jeremie D. Pikus; William M. Westler; John L. Markley; Brian F. Volkman; Brian G. Fox (JBIC Journal of Biological Inorganic Chemistry, 2004)

Long-term population trends in widespread British moths - Kelvin F. Conrad; Ian P. Woiwod; Mark Parsons; Richard Fox; Martin S. Warren (Journal of Insect Conservation, 2004)

Hepatic EROD Activity is Not a Useful Biomarker of Polychlorinated Biphenyl Exposure in the Adult Herring Gull (Larus argentatus) - Sean W. Kennedy; Glen A. Fox; Stephanie P. Jones; Suzanne F. Trudeau (Ecotoxicology, 2003)

Assignment of RFLP linkage groups to chromosomes using monosomic F1 analysis in hexaploid oat - S. L. Fox; E. N. Jellen; S. F. Kianian; H. W. Rines; R. L. Phillips (Theoretical and Applied Genetics, 2001)

The effects of tail loss on survival, growth, reproduction, and sex ratio of offspring in the lizard Uta stansburiana in the field - S. F. Fox; J. K. McCoy (Oecologia, 2000)

Geographic Variation in Hematological Variables in Adult and Prefledgling Herring Gulls ( Larus argentatus ) and Possible Associations with Organochlorine Exposure - K. A. Grasman; P. F. Scanlon; G. A. Fox (Archives of Environmental Contamination and Toxicology, 2000)

Reproductive and Physiological Effects of Environmental Contaminants in Fish-Eating Birds of the Great Lakes: A Review of Historical Trends - Keith A. Grasman; Patrick F. Scanlon; Glen A. Fox (Environmental Monitoring and Assessment, 1998)

Mutational analysis of the GDNF/RET-GDNFRα signaling complex in a kindred with vesicoureteral reflux - Sarah E. Shefelbine; Sangeeta Khorana; Pamela N. Schultz; Eileen Huang; Nicole Thobe; Zheng J. Hu; Gary M. Fox; Shuqian Jing; Gilbert J. Cote; R. F. Gagel (Human Genetics, 1998)

Acceleration of cheese ripening - P. F. Fox; J. M. Wallace; S. Morgan; C. M. Lynch; E. J. Niland; J. Tobin (Antonie van Leeuwenhoek, 1996)

Genetics of a tissue esterase polymorphism (Est-6) in the rabbit (Oryctolagus cuniculus) - L. F. M. van Zutphen; M. G. C. den Bieman; O. von Deimling; R. R. Fox (Biochemical Genetics, 1987)

Purification of human leukocyte interferon alpha by Carboxymethyl Controlled Pore Glass bead chromatography - I. Mecs; D. Chin; F. Fox; Mathilde Krim (Archives of Virology, 1984)

Genetics of two tissue esterase polymorphisms (Est-4 and Est-5) in the rabbit - L. F. M. van Zutphen; R. R. Fox; M. G. C. W. den Bieman (Biochemical Genetics, 1983)

Separation of β-d-galactosidases in rabbit tissues: Genetics of neutral β-d-galactosidase - L. F. M. van Zutphen; M. G. C. W. den Bieman; R. R. Fox (Biochemical Genetics, 1983)